Distribution of Size of Banggai Cardinal Fish Pterapogon kauderni Koumans, 1933 in the Front Waters of Dudepo, South Bolaang Mongondow Regency - Pongajouw, Oxha Putra; Rondonuwu, Ari B.; Bataragoa, Nego E.; Kalesaran, Ockstan; Lohoo, Anneke V.; Salaki, Meiske S. (Jurnal Ilmiah Platax, 2022)
Â This study aims to determine the distribution of sizes and morphological characters of Banggai Cardinal fish in the waters in front of Dudepo Village, South Bolaang Mongondow Regency. Field data collection using the explorer survey method with diving and snorkeling activities. Fishing in each microhabitat with â€œSibuâ€ fishing gear. The size distribution of cardinal Banggai fish is in the range of 2.7 - 9.2 cm. The size of the male Banggai Cardinal fish is in the range of 3.8 - 9.2, while the female is in the range of 3.7 - 8.1 cm. The size of fish in symbiosis with anemones is in the range of 2.7 - 7.1 cm, while those in sea urchins are in the range of 4.8 - 9.2 cm.Keywords: Size Distribution; Banggai Cardinal fish; morphological charactersAbstrakPenelitian ini bertujuan untuk mengetahui sebaran ukuran dan karakter morfologi ikan banggai kardinal di perairan Desa Dudepo, Kabupaten Bolaang Mongondow Selatan. Pengambilan data lapangan menggunakan metode survei jelajah dengan kegiatan penyelaman dan snorkling.Â  Penangkapan ikan di setiap mikrohabitat, dengan alat tangkap â€œSibuâ€.Â  Sebaran ukuran ikan banggai kardinal berada pada kisaran 2,7 - 9,2 cm.Â  Ukuran ikan banggai kardinal jantan berada pada kisaran 3,8 - 9,2, sedangkan betina berada pada kisaran 3,7 - 8,1 cm.Â  Ukuran ikan yang bersimbiosis dengan anemon berada pada kisaran 2,7 - 7,1 cm, sementara yang berada di bulu babi berkisar 4,8 - 9,2 cm.